2014
DOI: 10.1089/ars.2014.5843
|View full text |Cite
|
Sign up to set email alerts
|

The PTEN/NRF2 Axis Promotes Human Carcinogenesis

Abstract: Aims: A recent study conducted in mice reported that liver-specific knockout of tumor suppressor Pten augments nuclear factor (erythroid-derived 2)-like 2 (NRF2) transcriptional activity. Here, we further investigated how phosphatase and tensin homolog deleted on chromosome 10 (PTEN) controls NRF2 and the relevance of this pathway in human carcin ogenesis. Results: Drug and genetic targeting to PTEN and phosphoproteomics approaches indicated that PTEN leads to glycogen synthase kinase-3 (GSK-3)-mediated phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 59 publications
6
102
0
4
Order By: Relevance
“…We clearly showed that metformin upregulated the Nrf2 system, while LPS treatment downregulated the Nrf2 system in both HFD-fed mice and HepG2 cells ( Figure 3C and 3D, Supplementary Figure 2 and 3). These results are in line with previous reports showing the interactions of the effects of metformin and LPS on the Nrf2 system [34,35] . The underlying regulatory mechanisms of LPS on the Nrf2 system were not addressed in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We clearly showed that metformin upregulated the Nrf2 system, while LPS treatment downregulated the Nrf2 system in both HFD-fed mice and HepG2 cells ( Figure 3C and 3D, Supplementary Figure 2 and 3). These results are in line with previous reports showing the interactions of the effects of metformin and LPS on the Nrf2 system [34,35] . The underlying regulatory mechanisms of LPS on the Nrf2 system were not addressed in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…The reciprocal regulation between Nrf2 system function and PTEN expression has been suggested by several studies [34,40] . In this study, by using an Nrf2 inhibitor, we found that Nrf2 is causally involved in the effect of metformin on the regulation of PTEN and insulin signaling (Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One of these phosphatases is PTEN (Lee et al, 2002;Kitagishi and Matsuda, 2013;Han et al, 2015). The catalytic C124 residue of PTEN can be modified through adduct formation with strong electrophiles such as CDDO-Im (Pitha-Rowe et al, 2009) and tertbutylhydroquinone (Rojo et al, 2014b). Then, the increased activation of the PI3K/AKT pathway involves inhibition of GSK-3 and subsequent stabilization of NRF2 (Fig.…”
Section: A Electrophilic Nuclear Factor (Erythroid-derived 2)-likementioning
confidence: 99%
“…I/R-induced Nrf2 activation directly upregulates estrogen sulfotransferase and in turn increases estrogen breakdown, limiting Nrf2 activity and gender-dependently affecting I/R injury (Guo et al, 2015). In addition, the crosstalk of Nrf2 signaling with the PTEN-GSK-3-b-TrCP pathway and the p62-mediated autophagy pathway has been demonstrated (Komatsu et al, 2010;Ni et al, 2014;Rojo et al, 2014;Taguchi et al, 2014). Han et al (2014) uncovered an ERa/liver X receptor (LXR)/ sterol regulatory element-binding protein (SREBP) 1 pathway modulating hepatic lipid metabolism (Han et al, 2014).…”
Section: Crosstalk Of Nrf2 and Estrogen Signaling In Lipid Metabolismmentioning
confidence: 99%